2020
DOI: 10.1177/1591019920956405
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the breach in Latin America: A pilot study of mechanical thrombectomy in the public healthcare system in Chile

Abstract: Background Mechanical Thrombectomy (MT) is the standard of care for treatment of large vessel occlusion stroke. Until the beginning of 2020 MT was not funded nor widely implemented at the public healthcare level in Chile. Objective To describe the results of a pilot program created to provide access to public MT in Santiago - Chile. Methods Analysis from a prospectively collected database of MT cases performed between September 2017 and September 2019 in one center. A stroke network was developed with a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
(18 reference statements)
0
4
0
2
Order By: Relevance
“…Este estudio corresponde a una experiencia de implementación de trombectomía mecánica en un hospital público chileno durante 7 años que se suma a otras recientes publicaciones que exponen el desarrollo de Tmec en servicios públicos de latinoamérica y que han obtenido resultados favorables 24,25 .…”
Section: Discussionunclassified
“…Este estudio corresponde a una experiencia de implementación de trombectomía mecánica en un hospital público chileno durante 7 años que se suma a otras recientes publicaciones que exponen el desarrollo de Tmec en servicios públicos de latinoamérica y que han obtenido resultados favorables 24,25 .…”
Section: Discussionunclassified
“…The implementation of mechanical thrombectomy occurred in a small number of hospitals in all countries and remains mostly restricted to private hospitals. Chile has had thrombectomy as a government policy with official reimbursement to public hospitals since January 2020 2 (29). The RESILIENT trial (30), a randomized thrombectomy trial across stroke centers in the Brazilian Public Healthcare System, demonstrated the safety, efficacy, and cost-effectiveness of this treatment in underresourced settings.…”
Section: Discussionmentioning
confidence: 99%
“…This is a retrospective analysis of a prospectively collected database comparing two cohorts of patients treated within our MT program at the Instituto de Neurocirugia Dr. Asenjo (INCA) in Chile. Our program, as shown in a previous publication [15] is based on a large stroke network with one MT capable center (INCA) and five referring hospitals, with neurologists, stroke care and intravenous thrombolysis (IVT) capacity, in a metropolitan area in Santiago, covering approximately 3.3 million inhabitants from 3 different public administrative health areas. These referral centers transfer patients with MT criteria using a drip and ship model.…”
Section: Methodsmentioning
confidence: 99%